Kant and idealism - Rockmore, Tom, 1942- (Yale University Press, 2007)
This much-needed book examines one of the great lacunae of contemporary philosophical discussion - idealism. Addressing the widespread confusion about the meaning and use of the term, Tom Rockmore surveys and classifies some of its major forms. He argues that Kant provides the essential link between three main types of idealism associated with Plato, the new way of ideas, and German idealism. The author also makes a case for the contemporary relevance of at least one strand in the tangled idealist web, a strand most clearly identified with Kant. In terms of the philosophical tradition, Rockmore contends, constructivism offers a lively, interesting, and important approach to knowledge after the decline of metaphysical realism.